2018
DOI: 10.1177/0960327117751235
|View full text |Cite
|
Sign up to set email alerts
|

Protective mechanisms of 6-gingerol in dextran sulfate sodium-induced chronic ulcerative colitis in mice

Abstract: Ulcerative colitis (UC) is a relapsing and remitting inflammatory disease of the colon, with an increasing incidence worldwide. 6-Gingerol (6G) is a bioactive constituent of Zingiber officinale, which has been reported to possess various biological activities. This study was designed to evaluate the role of 6G in chronic UC. Chronic UC was induced in mice by three cycles of 2.5% dextran sulfate sodium (DSS) in drinking water. Each cycle consisted of 7 days of 2.5% DSS followed by 14 days of normal drinking wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 58 publications
0
31
0
2
Order By: Relevance
“…231 However, the evaluation of 6-gingerol on DSS-induced chronic ulcerative colitis revealed that oral administration of 6-gingerol (100 mg/kg) inhibited the disease activity index (combined scores of stool consistency, rectal bleeding body weight loss, and stool consistency) and formation of aberrant crypt foci in rats. 232 It is necessary to mention that aberrant crypt foci are tube-similar glands forming abnormal conditions in the rectum and colon. It is the earliest symptom of cancer beginning, which is created before colorectal polyps.…”
Section: Miscellaneousmentioning
confidence: 99%
“…231 However, the evaluation of 6-gingerol on DSS-induced chronic ulcerative colitis revealed that oral administration of 6-gingerol (100 mg/kg) inhibited the disease activity index (combined scores of stool consistency, rectal bleeding body weight loss, and stool consistency) and formation of aberrant crypt foci in rats. 232 It is necessary to mention that aberrant crypt foci are tube-similar glands forming abnormal conditions in the rectum and colon. It is the earliest symptom of cancer beginning, which is created before colorectal polyps.…”
Section: Miscellaneousmentioning
confidence: 99%
“…It has diverse and interesting pharmacological effects including antipyretic, anti‐inflammatory, anti‐angiogenic, anti‐cancer, cardio‐tonic, and anti‐aging effects. It inhibits spontaneous motor activity and prostaglandin biosynthesis (Ajayi, Adedara, & Farombi, ; Dugasani et al, ; Kim et al, ; Kiuchi, Iwakami, Shibuya, Hanaoka, & Sankawa, ; Lee et al, ; Lee, Seo, Kang, & Kim, ; Lv et al, ; Suekawa et al, ; Tahir et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the duration of 6-Gingerol compounds available in the colon was up to 12 h, which may favor their antioxidant potential and healthy effects (Majdoub et al, 2019). Moreover, 6-gingerol could prevent DSS-induced chronic UC via anti-inflammatory and antioxidative mechanisms and preservation of the Wnt / β-catenin signaling pathway (Ajayi et al, 2018). 6-gingerol also improved ulceration and bleeding in the gastrointestinal tract caused by aspirin (Zhu et al, 2017).…”
Section: Introductionmentioning
confidence: 97%